Acute Lymphocytic Leukemia with Prominent Azurophilic Granulation and Punctate Acidic Nonspecific Esterase and Phosphatase Activity. Issue 5 (1st February 2016) - Grogan, Thomas M.; Insalaco, Samuel J.; Savage, Richard A.; Vail, Michael L
Abstract : Cytochemical, ultrastructural, and terminal deoxynucleotidyl transferase determinations in three cases of acute lymphocytic leukemia with azurophilic granules and punctate alpha-naphthyl acetate esterase (ANAE), alphanapthyl butyrate esterase (ANBE), and acid phosphatase (AP) activities further described a cytochemical and morphologic variant of acute lymphocytic leukemia. The ANAE, ANBE, and AP activities appeared specifically localized within cytoplasmic granules. Electron microscopy substantiated a prominence of membrane-bound dense-core cytoplasmic granules. The variegated appearance of these dense-core granules and the cytochemical profile suggest that the aberrant granules are lysosomal in nature. Both the prominent cytoplasmic granules and the older age distribution led to early misdiagnosis of myelocytic leukemia. The distinctive cytochemical/morphologic profile and the ease of misdiagnosis suggest an important morphologic variant of acute lymphocytic leukemia.